Public Knowledge, Attitudes and Behavior Regarding the Covid-19 Pandemic - Syahrini, Ardini (Universitas Ibn Khaldun Bogor, 2025)
In December 2019, a new type of corona virus was discovered called Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). This disease is known to first appear in Wuhan, China in December 2019 (WHO, 2020). This viral infection is called COVID-19 and is more dangerous than SARS or MERS. The purpose of this study was to determine the knowledge and attitudes of the community regarding COVID 19. This study was a quantitative study with a cross sectional design, the knowledge of the community regarding COVID 19 was said to be good because it was able to answer the questionnaire instrument correctly. The community hopes that this epidemic will end soon so that they can carry out their activities as usual. It is necessary to disseminate information related to COVID 19 to the wider community, the main symptoms. COVID-19 diseases include cough, fever, and shortness of breath. This disease affects all groups, adults, the elderly, and children.